A systematic literature review of Intensive Care Unit (ICU)Nurses' Experience During Covid-19 - Nur Mursyidah, Abdul Hamid; Mohamad Firdaus, Mohamad Ismail; Siti Zuhaidah, Shahadan; Salizar, Mohamed Ludin; Tuan Sidek, Tuan Muda; Nazri, Mohd-Yusof (Asia Pacific Higher Learning Sdn Bhd., Lincoln University College, 2023)
Numerous studies agree that intensive care unit (ICU) nurses carry a relatively heavy mental and physical load, which may be attributable to the gravity of their responsibilities in an environment where the slightest error could have catastrophic effects on the lives of the patients in their care. New insights are needed to support ICU nurses during the pandemic by recognizing their experiences and challenges in work environments. Hence, conducting a systematic literature review may provide a better understanding of the common challenges that ICU nurses experienced during COVID-19 and provide research-based evidence of effective adaptation strategies that have been implemented to lessen their burden. Objective: The impact of the 2019 COVID season on the work of intensive care unit (ICU) nurses is the subject of this review. Methods: A systematic literature review was performed on three electronic search engines, which are Scopus, ProQuest, and Google Scholar, from 2019 to 2022. A PRISMA flow chart was used to facilitate the process of article selection. Results: A total of 12 articles were selected for the review; the main themes were: i) The challenges in taking care of patients; ii) Adaptation strategies; iii) The impact of COVID-19 on social life; and iv) The impact of COVID-19 on perceptions of career. Conclusion: Given the challenges faced by ICU nurses during the COVID-19 pandemic, it is essential for healthcare institutions and policymakers to provide adequate support systems. This includes access to mental health resources, counseling services, and peer support programs to help nurses cope with the emotional and psychological stress associated with their work during a crisis. Even though this review attempted to identify the adaptation strategies used by ICU nurses, there are currently fewer studies investigating this issue. Hence, further study should explore this.